Glucose Metabolism, Insulin Sensitivity and β-Cell Function in Type A Insulin Resistance Syndrome Around Puberty: A 9-Year Follow-up - Huang, Z.; Liu, J.; Ma, L.; Wan, X.; He, X.; Fang, D.; Liao, Z.; Li, Y. (Hormone and Metabolic Research, 2014)
Diabetes mellitus is thought to be progressive. Insufficient insulin secretion in compensation for insulin resistance leads to glucose intolerance. A previously reported proband with type A insulin resistance syndrome and her younger twin brothers with and without the R1174W missense mutation in the insulin receptor gene were followed for 9 years to study the progression of glucose metabolism, insulin sensitivity, and β-cell function around puberty. Five-hour OGTT was performed in them at each visit. Areas under the curves of glucose, insulin and C-peptides, insulinogenic index, AIR, and Homa indices were assessed. Intramyocellular lipids (IMCLs) were quantified in the proband and compared to those of 12 nondiabetic subjects, 118 newly diagnosed type 2 diabetic patients. The proband maintained normal HbA1c (27–37 mmol/mol) and fasting plasma glucose (3.7–4.5 mmol/l), and her glucose tolerance ameliorated over years. The proband’s Homa-IR decreased into adulthood, while her Homa-B, insulinogenic index, AIR, AUCs of insulin, and C-peptide decreased accordingly. Homa-B to Homa-IR ratios stayed significantly higher than normal. Homa-B, AUCs of insulin, and C-peptide of the twin brothers increased in response to the increment of Homa-IR as they entered middle and late puberty. The changes were more dramatic in the twin brothers carrying the mutation. IMCLs of the proband were lower than those of the nondiabetic counterparts and were disproportional for the degree of insulin resistance. Our longitudinal data of type A insulin resistance syndrome around puberty provide significant information for the study of insulin secretion in compensation for insulin resistance.
Keywords: insulin resistance; puberty; compensation; diabetes mellitus; intramyocellular lipid